TUDY REGARDING SHARE OF PERI-IMPLANT BONE AUGMENTATION TECHNIQUES AND MATERIALS - Bianca Törok; Roland Törok; Forna Norina (Romanian Society of Oral Rehabilitation, 2020)
The study aimed to assess the distribution of periimplant augmentation techniques and graft materials in relation to demographic factors and local parameters. Materials and method. In a study group of 100 edentulous patients candidate to dental implants it was investigated the share of bone augmentation techniques and graft materials in relation to age groups, edentation localization (maxillary vs mandibular; dental groups); alveolar bone resorption degree. Results. GBR technique was mostly used with highest shares as follows: 92,3% for maxillary implant sites in age group 50-59, 78,3% for maxillary implant sites in areas of molars and premolars, all implant sites Misch class B. Conclusions. Traditional GBR was the most used addition technique, followed by SGBR and block transplant for all age groups, localization and alveolar bone resorption degrees. Xenografts were the most used augmentation materials for all categories of alveolar bone resorption.